Jungle of stone : the extraordinary journey of John L. Stephens and Frederick Catherwood, and the discovery of the lost civilization of the Maya - Carlsen, William, 1945- (William Morrow, an imprint of HarperCollins Publishers, 2016)
Documents the true story of the nineteenth-century rediscovery of the Mayan civilization by American ambassador John Lloyd Stephens and British architect Frederick Catherwood, illuminating how their findings profoundly changed Western understandings about human history.